The Correlation Between Body Composition and Mini Nutritional Assessment in The Elderly: A Cross-Sectional Study - Frisca Frisca; Alexander Halim Santoso; Fiona Valencia Setiawan; Naufal Rayhan; Louise Audrey Sukianto (Jurnal Kesehatan Amanah, 2025)
Aging leads to changes in body composition influenced by physical, psychological, and social factors. Understanding the relationship between fat distribution and nutritional status, particularly in older adults, is crucial for targeted interventions. This study examines the impact of body fat composition on nutritional assessment, particularly its influence on MNA scores in older adults. It aims to provide insights into how fat distribution and related metabolic changes affect nutritional status and inform targeted interventions for aging populations. The sample consisted of 31 elderly woman subjects selected through purposive sampling in a cross-sectional design from St. Francis of Assisi Catholic Church. Their nutritional status was determined using the MNA score, and the body composition measures were total body fat and skeletal muscle measured by the Omron Karada Scan HBF 375. SPSS analyzed statistical differences between body composition and MNA scores. This study found significant correlations between the Mini Nutritional Assessment scores and body composition parameters, including BMI (r = 0.473, p = 0.007), total subcutaneous fat (r = 0.468, p = 0.008), and visceral fat (r = 0.457, p = 0.010). Arm skeletal muscle showed a negative correlation (r = -0.486, p = 0.006). These results emphasize that fat composition is a critical determinant of nutritional status in the elderly. The study found a significant correlation between fat composition as a key determinant of nutritional status in the elderly, with significant correlations observed between MNA scores and various body fat parameters. Keywords: Body Composition, Elderly, Mini Nutritional Assessment